Erlebte Modelle - Kunsthalle Bern, Bern; Kurzmeyer, Roman (Zürich : Voldemeer AG, 2000)
Buser, Renate ; Sester, Marie ; Wright, Elizabeth ; Grosse, Katharina ; Fankhauser, Susanne ; Rossiter, Sarah ; Lee, Bul ; Klein, Martina ; home, a ; Brand, Heinz ; Schaerf, Eran ; Gallaccio, Anya
biografie
Erlebte Modelle / Model Experience, Projektraum, Kunsthalle Bern 1998-2000
Duits
Engels
boek